A randomized clinical trial of oral steroids for ulnar neuropathy in type 1 and type 2 leprosy reactions - Garbino, José Antonio; Virmond, Marcos Da Cunha Lopes; Ura, Somei; Salgado, Manoel Henrique; Naafs, Bernard (FapUNIFESP (SciELO), 2008)
Background: Steroids regimens in leprosy neuropathies are still controversial in botth types of reactions. Method: For this trial, 21 patients with ulnar neuropathy were selected from 163 leprosy patients, 12 with type 1 reaction (T1R) and nine with type 2 (T2R). One experimental group started with prednisone 2 mg/kg/day and the control group with 1 mg/kg/day. A clinical score based on tests for spontaneous pain, nerve palpation, sensory and muscle function was used. Neurophysiological evaluation consisted on the motor nerve conduction of the ulnar nerve in three segments. Student t test for statistical analysis was applied on the results: before treatment, first week, first month and sixth month, between each regimen and types of reaction. Conclusion: In both reactions during the first month higher doses of steroids produced better results but, earlier treatment with lower dose was as effective. Short periods of steroid, 1 mg/Kg/day at the beginning and,tapering to 0,5 mg/Kg/day or less in one month turned out to be efficient in T2R.
Keywords: Leprosy; Neurophysiology; Steroids; Ulnar neuropathy